The influence of resistance training on endurance performance in female endurance cyclists - Bishop, D.; Jenkins, D. J.; MacKinnon, L. T.; Carey, M. F.; McEniery, M (Medicine & Science in Sports & Exercise, 1997)
The purpose of this study was to determine the effects of resistance training on endurance performance in female endurance cyclists. Ss were assigned to a resistance training (N = 14) and a control group (N = 7). Resistance training focusing on leg strength consisted of training twice per week for 12 weeks. There were no significant changes in either group in a one-hour cycle test, lactate threshold, peak VO2, or muscle fiber characteristics. Implication: Increased leg strength derived from resistance training does not improve endurance performance in female endurance cyclists.